2021
DOI: 10.3390/molecules26154464
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants Isolated from Elaeagnus umbellata (Thunb.) Protect against Bacterial Infections and Diabetes in Streptozotocin-Induced Diabetic Rat Model

Abstract: The increase in resistance of microbes against conventional drugs is currently a hot issue, whereas diabetes is another main cause of mortalities encountered throughout the world after cancer and heart attacks. New drug sources in the form of plants are investigated to get effective drugs for the mentioned diseases with minimum side effects. Elaeagnus umbellata Thunb. is a medicinal plant used for the management of stress related disorders like diabetes and other health complications. The active constituents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The antioxidants in plants have become a hotspot for researchers in recent decades due to the mentioned fact of low or no side effects. Studies have indicated that the use of natural antioxidants can reduce oxidative stress and reduce the risk of major human diseases, including oxidative stress [ 3 , 6 ]. The n -hexane fraction, crude extract, and fraction B were more potent against DPPH radicals, whereas against ABTS, the n -hexane fraction and fraction A were more potent, indicating that these extracts contained certain phytoconstituents capable of scavenging free radicals, which could thus be further investigated for the isolation of responsible compounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The antioxidants in plants have become a hotspot for researchers in recent decades due to the mentioned fact of low or no side effects. Studies have indicated that the use of natural antioxidants can reduce oxidative stress and reduce the risk of major human diseases, including oxidative stress [ 3 , 6 ]. The n -hexane fraction, crude extract, and fraction B were more potent against DPPH radicals, whereas against ABTS, the n -hexane fraction and fraction A were more potent, indicating that these extracts contained certain phytoconstituents capable of scavenging free radicals, which could thus be further investigated for the isolation of responsible compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The antidiabetic properties of A. articulata crude extracts and fractions ( Figure 7 and Table S8 ) were determined based on the inhibitory effect against two carbohydrate hydrolyzing enzymes, namely α-amylase and α-glucosidase. As mentioned before, starch is converted into disaccharides and oligosaccharides by pancreatic α-amylase, while disaccharides are broken down into glucose by intestinal α-glucosidase [ 3 , 6 ] and, thus, if inhibited, will lessen the glucose burden in diabetic patients as their inhibition could retard the breakdown of starch in the gastrointestinal tract and, therefore, would ameliorate hyperglycemia in human. The detected compounds are known to be antioxidant and antidiabetic agents, as indicated in the previously reported studies [ 3 , 6 , 9 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extracts of green pertained from Camellia sinensis species under Theaceae family bearing several kinds of secondary metabolites, for example, catechins, anthocyanin (Liao et al, 2021), caffeine (Parvez et al, 2021), Gallic acids (Jovanovic et al, 2021), etc. Flavan 3-ols, namely catechins, is also known as the principal element of polyphenols in the young shoot of tea plants (Guo et al, 2017) with high anti-oxidant and reduced the high level of blood glucose, various kinds of renal function, hepatic and lipid parameters in animals (Nazir et al, 2021). By adding extra anti-oxidant substances, the human body uses them safely and has extracted them from food and plants (Bae et al, 2020).…”
Section: Introductionmentioning
confidence: 99%